PRECISE ATOMIC MASS DETERMINATIONS WITH DOUBLE-FOCUSING MASS SPECTROMETER - Isenor, Neil Raymond (My University, 1959)
A new large double-focusing mass spectrometer and its application to the determination of precise atomic mass values are described. A peak-matching technique is described by which mass difference values are obtained from voltage measurements. The mass values obtained for Sr86, Sr88 and Zr90 have largely resolved the discordance which had existed between the nuclear transmutation data and mass spectroscopic data in that region of the atomic mass table.
Keywords: Atomic Mass; Spectrometer; Double-focusing; Voltage